Pelatihan Penggunaan Media Kongkret dalam Penanaman Konsep pada Operasi Hitung Bilangan Bulat - I Nyoman Murdiana; Sukayasa; Muh. Hasbi (Jurnal Kreatif Online, 2022)
The purpose of implementing this service is (1) to strengthen the ability of elementary school teachers in using concrete media to instill the concept of integer operations (2) the mistakes made by trainees in using concrete media to instill the concept of integer operations. The participants of this training were teachers of SD Gugus V, East Palu District with a total of 25 participants. The service method used is presentation, demonstration, training and question and answer. The results of the service implementation show that all participants are very enthusiastic about participating in this training activity, and all training participants have obtained strengthening abilities to use concrete in learning integer arithmetic operations. However, the findings of the questionnaire showed that there were still trainees who experienced errors in using the posinega card and number line media. Errors in using posinega cards occur in subtraction operations, namely the use of neutral cards so that subtraction operations can be carried out. While using the number line, the error found is not changing the direction of the arrow when the operation is subtraction. If the arrows are not changed, then the forward (addition) and backward (subtract) steps will result in an error. Respondents also still find it difficult to distinguish the sign of the subtraction operation from the sign of a number (negative number), so that when the respondent is working on subtracting positive and negative integers or negative and negative integers, there are still many respondents who make the wrong number line demonstration.